Pelatihan Pangan Fungsional: Susu Kurma dengan Garam Himalaya untuk Cegah Stunting - Yanuan, Mohammad Edwinsyah; Wati, Cicik Retno; Sholihah, Elis Rahmawati Mar’atus; Al Ayyubi, Waridad Umais (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service activity aims to enhance the understanding and skills of the residents of Dempel Village, Geneng Subdistrict, Ngawi Regency, in utilizing functional foods to support stunting reduction. The main focus is on training participants to produce high-nutrient date milk enriched with Himalayan salt, specifically targeted at pregnant women and members of the PKK women’s group. The team from PSDKU Agribusiness Management Campus 5 Ngawi provided education through counseling and hands-on practice in date milk production. This community service activity was conducted on January 16, 2025, in Dempel Village, Geneng Subdistrict, Ngawi Regency, attended by 20 pregnant women and PKK members. The outcome of this program was the successful understanding of the steps to produce date milk with Himalayan salt, enabling participants to independently replicate the process. In addition to contributing to stunting prevention efforts, this activity also serves as a foundational idea and creates new business opportunities for the community by developing economically valuable local products.